2015
DOI: 10.1002/asi.23461
|View full text |Cite
|
Sign up to set email alerts
|

Science communication and dissemination in different cultures: An analysis of the audience forTEDvideos inChina and abroad

Abstract: Disseminated across the world in more than 100 languages and viewed over 1 billion times, TED Talks is a successful example of web-based science communication. This study investigates the impact of TED Talks videos on YouKu, a Chinese video portal, and YouTube using 6 measures of impact: number of views; likes; dislikes; comments; bookmarks; and shares. In particular, we study the relationship between the topicality and impact of these videos. Findings demonstrate that topics vary greatly in terms of their imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
3
0
2
Order By: Relevance
“…It should be noted that audiences with different cultures have different preferences with regard to TED Talk topics. Pan et al (2016) investigated the TED Talks viewed on YouKu (a Chinese video website) and YouTube and found that topics on global issues and technology were more popular on YouKu, whereas topics on entertainment and psychology/philosophy were more popular on YouTube.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It should be noted that audiences with different cultures have different preferences with regard to TED Talk topics. Pan et al (2016) investigated the TED Talks viewed on YouKu (a Chinese video website) and YouTube and found that topics on global issues and technology were more popular on YouKu, whereas topics on entertainment and psychology/philosophy were more popular on YouTube.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the content of the Astronomy theme is the furthest away from people's lives, people pay relatively little attention to this topic. This further illustrates that Tik Tok reaches a larger audience in the lower market [21].…”
Section: Topical Differences In Time Creator and Textual Featuresmentioning
confidence: 72%
“…Benefícios identificados neste estudo quanto à publicação de videoartigos sugerem que a evolução da comunicação social por vídeo tem provocado uma reflexão entre os acadêmicos, no sentido de valorizarem o formato audiovisual como recurso legítimo para disseminação científica. Isso também se alinha ao fato de que os videoartigos têm sido mais difundidos em áreas de pesquisa de CS (Pan;Hua, 2016). Além do já citado, Barros (2015) salienta como benefício o impacto nas altmetrics e o potencial para incrementar a divulgação do conhecimento científico, ou seja, valorizar esse olhar para fora.…”
Section: Análise Dos Resultadosunclassified
“…Especificamente no tocante aos benefícios dos videoartigos, destaca-se que estes propõem uma nova dinâmica para abordar problemas complexos, detalhes metodológicos e práticas do fazer ciência (Kousha;Theiwall;Abdoli, 2012). Ademais, têm reflexos na visibilidade que afeta cientistas e instituições de pesquisa (Berkowitz, 2013;Rosenthal, 2018); contribuem para incrementar as métricas de produção científica ao complementar um artigo escrito (Ferreira et al, 2021); promovem mais repercussão junto ao público quando exibem cientistas versus não cientistas (Rosenthal, 2020); e vêm ganhando mais atenção em áreas como ciências ambientais, ciências da saúde e biotecnologia (Pan;Hua, 2016). O próprio aumento expressivo do número de citações de vídeos do YouTube como fontes de pesquisa e objeto de estudo (Kousha;Theiwall;Abdoli, 2012) motiva discussões sobre a relevância do uso dos vídeos científicos online como fonte fidedigna de informação científica (Damude et al, 2017;Ragimova;Loginov;Khorov, 2019;Boy;Burcher;Christ, 2020;Nagumo;Teles;Silva, 2020 Todavia, há controvérsias sobre certos benefícios e desconfiança de que o novo gênero seja aplicável com sucesso em determinadas áreas de conhecimento (Rosenthal, 2020;Entradas et al, 2020;Ruzi;Lee;Smith, 2021).…”
unclassified